Guidelines for the Management of Pediatric Severe Traumatic Brain Injury, Third Edition: Update of the Brain Trauma Foundation Guidelines, Executive Summary. Issue 6 (2nd March 2019) - Kochanek, Patrick M; Tasker, Robert C; Carney, Nancy; Totten, Annette M; Adelson, P David; Selden, Nathan R; Davis-O'Reilly, Cynthia; Hart, Erica L; Bell, Michael J; Bratton, Susan L; Grant, Gerald A; Kissoon, Niranjan; et al.
Abstract: The purpose of this work is to identify and synthesize research produced since the second edition of these Guidelines was published and incorporate new results into revised evidence-based recommendations for the treatment of severe traumatic brain injury in pediatric patients. This document provides an overview of our process, lists the new research added, and includes the revised recommendations. Recommendations are only provided when there is supporting evidence. This update includes 22 recommendations, 9 are new or revised from previous editions. New recommendations on neuroimaging, hyperosmolar therapy, analgesics and sedatives, seizure prophylaxis, temperature control/hypothermia, and nutrition are provided. None are level I, 3 are level II, and 19 are level III. The Clinical Investigators responsible for these Guidelines also created a companion algorithm that supplements the recommendations with expert consensus where evidence is not available and organizes possible interventions into first and second tier utilization. The complete guideline document and supplemental appendices are available electronically (https://doi.org/10.1097/PCC.0000000000001735 ). The online documents contain summaries and evaluations of all the studies considered, including those from prior editions, and more detailed information on our methodology. New level II and level III evidence-based recommendations and an algorithm provide additional guidance for the development of local protocols to treat pediatric patients with severe traumatic brain injury. Our intention is to identify and institute a sustainable process to update these Guidelines as new evidence becomes available.